2021
DOI: 10.1016/j.ijrobp.2021.07.688
|View full text |Cite
|
Sign up to set email alerts
|

Is Remote Learning as Effective as In-Person Learning for Contouring Education? A Comparison of Face-to-Face vs. Online Delivery of the Anatomy and Radiology Contouring Bootcamp

Abstract: Materials/Methods: All applicants provided demographic information and specific mentorship need requests. Pairings occurred periodically based on a personalized pairing process. This year, due to COVID-19, all sessions were held virtually. A questionnaire was designed in Google Forms based on the Society for Women in Radiation Oncology (SWRO) annual survey to evaluate the mentorship program. Data were collected and analysis was conducted using JMP version 15(SAS Institute Inc, Cary, NC). Results: Since June 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Thirty‐six medical schools were included in these studies with 1776 students participating in total. Only two studies enrolled medical residents along with the students: Eansor et al ( 2021 ) recruited medical and radiological residents and Fang et al ( 2014 ) included both medical and surgical residents. Twenty studies reported demographic information about the participants and 11 did not.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty‐six medical schools were included in these studies with 1776 students participating in total. Only two studies enrolled medical residents along with the students: Eansor et al ( 2021 ) recruited medical and radiological residents and Fang et al ( 2014 ) included both medical and surgical residents. Twenty studies reported demographic information about the participants and 11 did not.…”
Section: Resultsmentioning
confidence: 99%
“…For measurement of outcomes, two studies (Harrell et al, 2021 ; Nagaraj et al, 2021 ) lacked quantitative data for the outcomes for the control group and were classed as having an unclear risk of reporting bias. The case control studies were classed as low risk (De Faria et al, 2016 ; Eansor et al, 2021 ; Ikram & Rabbani, 2021 ; Yang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The population of students that anatomy educators are providing for is becoming more diverse in terms of age, gender, culture, and geography (Vnuk et al, 2017; Avci et al, 2019; Bliss et al, 2020; Eansor et al, 2022). Students are also showing increasing preferences and need to personalize their learning as they contend with additional and off‐campus commitments (Franzoi et al, 2021; Legan & Zupan, 2022).…”
Section: Future Outlooksmentioning
confidence: 99%